Intercultural communication for the global business professional
1 online resource
Keywords: "This text integrates business and communication concepts to immerse students in the global communication experiences of business professionals. The authors argue that the essentials of intercultural communication, such as nonverbal communication, conflict, meeting management, interviewing, and negotiations are most useful to burgeoning professionals when they are woven into discussions about economic systems, market forces, production processes, finance structures, and human resources priorities. Each chapter begins with an explanation of theories and key terms appropriate for introductory-level students in both business and communication, then supplements that discussion with examples that demonstrate the concepts at work. The cases chosen represent different market systems in both dominant and emerging economies, explaining the cultures of competitive markets with a global perspective rather than focusing on the US. This book ideal as a text for courses in international business or professional intercultural communication, or as a supplement for more general business and communication courses"--